Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3747/co.19.1020
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Uptake and Wait Times in Early-Stage Non-Small-Cell Lung Cancer

Abstract: at high resolution may optimize insights into emerging trends within cancer care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…Data from the Netherlands has shown a similar decrease in surgery and increase in the use of radiation in the presence of comorbidity, especially COPD [ 12 ]. While previous data has shown seemingly low rates of adjuvant chemotherapy among individuals with resected lung cancer in Canada [ 22 , 23 ], our study showed that individuals with COPD were somewhat less likely to receive adjuvant chemotherapy. Gao et al reported worse disease-free survival in their meta-analysis, although it was not possible to discern whether this was due to less aggressive curative therapy or differences in stage [ 8 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Data from the Netherlands has shown a similar decrease in surgery and increase in the use of radiation in the presence of comorbidity, especially COPD [ 12 ]. While previous data has shown seemingly low rates of adjuvant chemotherapy among individuals with resected lung cancer in Canada [ 22 , 23 ], our study showed that individuals with COPD were somewhat less likely to receive adjuvant chemotherapy. Gao et al reported worse disease-free survival in their meta-analysis, although it was not possible to discern whether this was due to less aggressive curative therapy or differences in stage [ 8 ].…”
Section: Discussioncontrasting
confidence: 86%